2021
DOI: 10.3389/fnmol.2021.634631
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Oral Administration of Brain Protein Combined With Probiotics Induces Immune Tolerance Through the Tryptophan Pathway

Abstract: Excessive inflammation leads to secondary immune damage after traumatic brain injury (TBI). The intestinal mucosa is a key component of immune tolerance due to gut-brain axis regulation, but the curative effect is not optimal. Intestinal dysfunction impairs the establishment of immune tolerance in patients with TBI. Therefore, we orally administered brain protein (BP) combined with probiotics to induce immune tolerance and explored the mechanism by which the homeostasis of the microbiota contributes to the enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Moreover, reduced abundance and evenness (Shannon, Simpson, and Fisher indices) of gut microbes were observed in CCI_M and CCI_F mice. These findings were also evident in a few earlier studies ( Du et al, 2021 ; Hou et al, 2021 ).…”
Section: Resultssupporting
confidence: 84%
“…Moreover, reduced abundance and evenness (Shannon, Simpson, and Fisher indices) of gut microbes were observed in CCI_M and CCI_F mice. These findings were also evident in a few earlier studies ( Du et al, 2021 ; Hou et al, 2021 ).…”
Section: Resultssupporting
confidence: 84%
“…Hou et al. show Akkermansia is significantly enriched in the patients with TBI and it increase at 3 days in surgical brain injury (SBI) rat, but the abundance of Akkermansia is decrease at 7 days and the mean is basically flat with healthy control; Furthermore, the oral administration of probiotics increases Akkermansia abundance at 3 days in SBI rat (in the supplementary results) ( 50 ). Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an observational study investigated the characteristics of gut microbiota in 101 TBI patients and found that organisms from rectal swabs obtained on days 0, 3, and 7 after admission belonged to the Proteobacteria phylum, with Enterobacteriaceae forming the largest group (90). Hou et al also analyzed the gut microbiota composition in a small cohort (10 healthy control volunteers vs. 24 TBI patients) and reported that the abundance of Enterococcus, Parabacteroides, Akkermansia, and Lachnoclostridium were significantly increased, while the abundance of Bifidobacterium and Faecalibacterium were decreased in TBI patients (91).…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%